A new understanding of punch-through shear testing. Issue 3 (20th March 2017) - Li, L. R.; Deng, J. H.; Liu, J. F.; Zheng, J.; Chen, T.; Deng, C. F.
Abstract : Shear strength is a very important mechanical parameter for rocks; thus, the accurate measurement of shear strength is a significant research topic in rock mechanics. A new method for testing rock shear strength, which is named the punch-through shear (PTS) testing has been proposed. This method can not only minimise the bending stress but can also effectively reduce the end effects. Appropriately fabricated white marble samples with a geometry that is favourable for obtaining accurate shear test results were used to verify the feasibility of the PTS-testing method for shear strength testing. The samples were tested using an MTS 815 servo-controlled rock mechanics test system without an applied confining pressure. Acoustic emission (AE) was captured by a PCI-2 acquisition system. The progressive failure process of the samples was investigated in the near-failure stage by way of macro-failure morphology, acquisition of force against axial displacement curves and AE. The results indicate that the samples appropriately undergo shear failure and that the axial force obtained at the moment when the force undergoes a sudden small drop prior to attaining the peak force, rather than the peak force, is appropriate for accurately calculating the shear strength.